2019
DOI: 10.1111/are.14467
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary protein source (fishmeal vs. plant protein) and non‐starch polysaccharide level on fat digestibility and faecal bile acid loss in rainbow trout (Oncorhynchus mykiss)

Abstract: This study investigated in rainbow trout (Oncorhynchus mykiss) if diet composition and feeding level affect faecal bile acid loss, and whether this reflects on the apparent digestibility coefficient (ADC) of fat. Six diets were formulated with either fishmeal or plant protein as main protein source. This created a contrast in the supply of bile acids, the bile acid precursor cholesterol, taurine and the taurine precursors (methionine + cysteine) involved in bile acid conjugation. For both protein sources, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
8
36
0
Order By: Relevance
“…Possibly, the lower feed intake (and thus faecal bile acid loss) of fish fed the high‐fat diets compared to the low‐fat diets could explain the presence of an NSP effect on fat ADC in the low‐fat diets while absent for the high‐fat diets. The same explanation holds when comparing the effects of NSP level on fat ADC and faecal bile acid loss of the current study with those of our previous studies (Staessen, Verdegem, Koletsi, et al (2020); Staessen, Verdegem, Weththasinghe, et al, 2020). The overall NSP effects in the current study were weaker compared to those previous studies, and most likely these NSP effects were dampened by the strong time‐related decrease in feed intake (i.e., faecal bile acid loss).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Possibly, the lower feed intake (and thus faecal bile acid loss) of fish fed the high‐fat diets compared to the low‐fat diets could explain the presence of an NSP effect on fat ADC in the low‐fat diets while absent for the high‐fat diets. The same explanation holds when comparing the effects of NSP level on fat ADC and faecal bile acid loss of the current study with those of our previous studies (Staessen, Verdegem, Koletsi, et al (2020); Staessen, Verdegem, Weththasinghe, et al, 2020). The overall NSP effects in the current study were weaker compared to those previous studies, and most likely these NSP effects were dampened by the strong time‐related decrease in feed intake (i.e., faecal bile acid loss).…”
Section: Discussionsupporting
confidence: 90%
“…Our previous studies showed that conditions that stimulate enhanced faecal bile acid loss (i.e., NSP level and feed intake) coincide with a reduction of fat ADC in rainbow trout (Staessen, Verdegem, Koletsi, et al (2020); Staessen, Verdegem, Weththasinghe, et al, 2020). A reduction of bile acid availability in the intestine was proposed to cause this reduction in fat ADC.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations